Overview of Roles of Novel Components in the Regulation of DNA Damage Repair in BRCA1-Deficient Cancers: An Update - Nhat Nguyen; Dominic Arris; Manh Tien Tran (DNA)
Cancers that arise from germline mutations of breast cancer associated gene 1 (BRCA1), which is a crucial player in homologous recombination (HR) DNA repair, are vulnerable to DNA-damaging agents such as platinum and PARP inhibitors (PARPis). Increasing evidence suggests that BRCA1 is an essential driver of all phases of the cell cycle, thereby maintaining orderly steps during cell cycle progression. Specifically, loss of BRCA1 activity causes the S-phase, G2/M, spindle checkpoints, and centrosome duplication to be dysregulated, thereby blocking cell proliferation and inducing apoptosis. In vertebrates, loss of HR genes such as BRCA1 and/or BRCA2 is lethal, since HR is a prerequisite for genome integrity. Thus, cancer cells utilize alternative DNA repair pathways such as non-homologous end joining (NHEJ) to cope with the loss of BRCA1 function. In this review, we attempt to update and discuss how these novel components are crucial for regulating DNA damage repair (DDR) in BRCA1-deficient cancers.